Nutri Edu Fun as Strategy to increase Knowledge of Health and Nutrition in the Community - Yusuf, Andi Mukramin; Alfiah, Elma; Puspa, Amalina Ratih; Prasetyawati, Annisa Dini; Orchidhea, Khalda Rahmah; Denaneer, Kyla; Rosyidi, Muhammad Naufal; Azzahra, Nabila Widya; Patricia, Wulandari (Media Karya Kesehatan, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition in the first 1000 days of life. The aim of implementing Nutri Edu Fun is to increase public awareness regarding the importance of a healthy and nutritious lifestyle, consuming halal food and thayyib to prevent stunting. Activities will be carried out on August - September 2023 in Cibening Village, Bekasi, West Java. The Nutri Edu Fun program consists of a village potential survey, Focus Group Discussion (FGD), collecting data on social mapping and household food security status, anthropometric measurements at posyandu, apart from that, additional activities are also carried out by PMT cooking competitions and demonstrations, follow-up FGDs at Cibening Village Office, and making the book "BERPANGKAL" (PMT Recipe Book with Local Food Ingredients). The results of measuring the food security status of 32 respondents in Cibening Village revealed that 13 respondents experienced food insecurity. After a Focus Group Discussion was conducted with stakeholders in Cibening Village, it was discovered that 6 toddlers were stunted. One of the reasons is that the provision of PMT (Additional Feeding) at Posyandu is still not optimal. The pre-test and post-test results showed that there was no significant increase in knowledge (p>0.05) after giving Nutri Edu Fun, this could be due to the fairly short duration of the intervention. However, it is hoped that the use of the Nutri Edu Fun module will become a source of information related to health and nutrition that is easy for the community to understand. Keywords: Food security, halal food and thayyib, stunting.